Cross-Dehydrogenative Coupling Reaction and Arylation of Quinoxalin-2(1H)-ones under Iodide/Peroxide Conditions - Wu, Yujuan; Chu, Xianglong; Yang, Di; Ma, Chen; Xie, Caixia (SynOpen, 2021)
A simple method has been developed for the synthesis of 3-(2-oxo-2-phenylethylidene)-3,4-dihydroquinoxalin-2(1H)-one and 3-aryl-quinoxalin-2(1H)-one derivatives through C–H activation of quinoxalin-2(1H)-ones by peroxides and iodide. In this protocol, the peroxide (TBPB) serves as both the radical initiator and aryl source, realizing arylation of quinoxalin-2(1H)-one in a one-step reaction. The methodology has the advantages of being a metal-free strategy and having broad functional group tolerance.
Keywords: C–H activation; iodide/peroxide system; metal-free; quinoxalin-2(1H)-one; radical process